Kinerja Satuan Polisi Pamong Praja dalam Pengawasan Pedagang Kaki Lima di Taman Kota Manis Pangkalan Bun Kabupaten Kotawaringin Barat - Syamsuri; Muhammad Roeis, Gusti; Sion, Holten; basrowi, basrowi (Center of Language and Cultural Studies, 2023)
The performance of the West Kotawaringin Regency Satpol PP in providing direction, guidance and supervision in structuring street vendors is not running effectively. even tend not to be able to overcome the problem of structuring street vendors. so that many street vendors commit violations due to the lack of guidance in structuring street vendors. The Satpol PP of Kotawaringin Barat Regency has carried out routine and periodic raids at the city park location against street vendors who are still selling in the area, but the awareness of street vendors not to repeat selling in the city park area is still repeated. The locus of this research is Taman Kota Manis Pangkalan Bun. This research was conducted using a qualitative method with a case study approach and data collection through observation, interviews and documentation. Supervision of street vendors in Taman Manis Pangkalan Bun can be seen from: repressive supervision, supervision techniques using direct observation or observation, the supervision process in accordance with SOPs, the nature and timing of periodic supervision through routine patrols and sudden supervision through operations and objective and comprehensive indicators as effective form of supervision